Influence of window openings’ architraves on forming a manor house’s image - A. A. Dedkova (Вестник СибАДИ)
The article is devoted to the research of the visual environment of stylistic decoration of a manor house on the example of designing carved wooden window architraves. There is studied a process of forming several widespread shapes and images of architraves. There is analyzed the stylistic decoration of Western Siberia’s manor on the example of forming historical manor development of the Cossack outer settlement. The considerable attention is paid to the one of the streets - Krasnykh Zor street. An attempt is made to reveal the main stylistic trends of designing window openings’ architraves of the manor development of the early twentieth century. In conclusion, the article presents general conclusions for further, more detailed study of this topic in the thesis.